Lactobacillus brevis 23017 Relieves Mercury Toxicity in the Colon by Modulation of Oxidative Stress and Inflammation Through the Interplay of MAPK and NF-κB Signaling Cascades - Jiang, Xinpeng; Gu, Shanshan; Liu, Di; Zhao, Lili; Xia, Shuang; He, Xinmiao; Chen, Hongyan; Ge, Junwei (Frontiers in Microbiology, 2018)
Lactobacillus strains have protective effects against heavy metals while relieving oxidative stress and modulating the immune response. Mechanisms that ameliorate heavy metal toxicity and the relationship between probiotics and gut barrier protection in the process of heavy metal pathogenesis was poorly understood. In this study, Lactobacillus brevis 23017(LAB, L.brevis 23017), a selected probiotics strain with strong mercury binding capacities, was applied to evaluate the efficiency against mercury toxicity in a mouse model. Histopathological results along with HE stains show that L. brevis 23017 protects the integrity of the small intestinal villus, which slows weight loss in response to Hg exposure. The qRT-PCR results demonstrate that L. brevis 23017 maintains a normal mucosal barrier via modulation of tight junction proteins. Importantly, the present study demonstrates that L. brevis 23017 effectively ameliorates injury of the small intestine by reducing intestinal inflammation and alleviating oxidative stress in animal models. Moreover, L. brevis 23017 blocks oxidative stress and inflammation through MAPK and NF-κB pathways, as shown by western blot. Together, these results reveal that L. brevis 23017 may have applications in the prevention and treatment of oral Hg exposure with fermented functional foods by protecting gut health in daily life.